River restoration in the urban landscape as a turning point in culture and hydropolitics: Narrations and case studies for the challenges of the 21 st century - Rzońca, Apolinary; Zamorowska, Karolina (Studia z Polityki Publicznej, 2024)
The purpose of this article is an interdisciplinary and cross-domain analysis of the idea of restoration of watercourses in urban landscapes. We refer to publications from the field of urban studies, ecohydrology and ecological humanities. In the first part of the article, we define the problem range and analyse the narrations of the artistic projects of the recent period dealing with blue infrastructure in cities. Next, we review case studies illustrating good practice in urban spaces involving the so-called urban-river concept. These examples will allow us to identify benefits to be found for cities, especially in the field of the fight on climate change. The article aims to outline possible solutions for the urban landscape, including opportunities to enrich the urban culture and identity.